Tanggung Jawab Tenaga Medis dan Rumah Sakit Terhadap Hak Akses Pelayanan Hemodialisa - Datuk Fachrul Razy (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The hospital provides for the responsibility of ensuring patients have appropriate and non-discriminatory access to such services. Hospitals provide the responsibility to provide education and information to patients regarding the dialysis process, benefits, risks, and preparation before and after the procedure. It aims to prove that it is the patient who can make the right decisions according to their needs. Research methods using normative juridical approach. The results of this study are: 1) management of patient access rights to health services has been established in the legislation. Law No. 39 of 1999 on Human Rights, Law No. 17 of 2023 on health, law of the Republic of Indonesia No. 40 of 2004 on the National Social Security System, and regulation of the Minister of Health No. 4 of 2017 on service tariff standards in the implementation of the Health Insurance Program, 2) health services at Type B hospitals in Semarang City and Regency are in accordance with human rights and 3) solutions to health service problems have been met by each hospital, among others, through the evaluation carried out by each hospital.